Neuro-endocrine mechanism of specific balneoeffects of sulfate-chloride sodium-magnesium mineral waters - Hrytsak, Myroslava; Popovych, Dariya; Ruzhylo, Sofiya; Zakalyak, Nataliya; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Background. Earlier we showed that the newly created sulfate-chloride sodium-magnesium drinking mineral waters “Myroslava” (5 g/L) and “Khrystyna” (10 g/L) have favorable effects on neuroendocrine-immune complex and metabolism of patients with their violations. At the same time, the influence of both waters on one constellation of parameters is similar, despite the twofold difference in mineralization, while on the other constellation it is different. The aim of this study was to elucidate the neuroendocrine mechanism of specific effects. Materials and Methods. The object of clinical-physiological observation were 22 men aged 23-70 years, who underwent rehabilitation treatment of chronic pyelonephritis and cholecystitis in remission in the Truskavets’ spa. The examination was performed twice, before and after a 7-10-day course of balneotherapy. All patients received bioactive water Naftussya, however, 11 men additionally drank water "Khrystyna", and the other 11 men - water "Myroslava". The subject of the study were the parameters of the neuroendocrine-immune complex and metabolism. Results. The method of canonical analysis shows that the changes in neuroendocrine factors (LF and VLF bands HRV; beta- and delta-rhythm-generating nerve structures, cortisol and aldosterone determine changes in the parameters of immunity, microbiota, metabolism and cholekinetics by 99,5-98,6%. Conclusion. The primary effects of mineral waters are the modulation of the activity of the structures of the central and autonomic nervous and endocrine systems, which, in turn, have a regulatory modulating effect on the immune system, microbiota, metabolism, cholekinetics and blood pressure.